TrkB Receptor Antagonism Enhances Insulin Secretion and Increases Pancreatic Islet Size in Rats Fed a Cafeteria-Style Diet - Jorge Agustín Velasco-Gutierrez; Elena Roces de Alvarez-Buylla; Sergio Montero; Alejandrina Rodríguez-Hernández; Saraí Limón Miranda; Karmina Martínez-Santillan; María del Rosario Álvarez-Valadez; Mónica Lemus; Alejandra Flores-Silva; Adolfo Virgen-Ortiz (Biomedicines)
Background: In recent years, the role of neurotrophins and their receptors in peripheral tissues has been of great interest. At a metabolic level, the brain-derived neurotrophic factor (BDNF) and its receptor trkB have been reported to participate in insulin secretion from the pancreas in response to increases in circulating blood glucose. Objetive: To determines the role of the BDNF-trkB pathway in insulin secretion and pancreatic morphology in rats fed a cafeteria-style diet for 16 weeks. Methods: For the study, male rats of the Wistar strain were divided into three groups as follows: (1) control group (standard diet), (2) CAF group (cafeteria-style diet) and (3) CAF group treated with ANA-12 (TrkB receptor antagonist). After 4 months of intervention, the glucose and insulin tolerance curves, serum insulin levels, body fat and hematoxylin-eosin staining pancreas were evaluated. Results: The results showed that the cafeteria-style diet induced an increase in the amount of body fat, alterations in the glucose tolerance curve, increased insulin circulation levels, increased HOMA indices and increased pancreatic islet size. The antagonism of the trkB receptor in the rats fed a cafeteria-style diet enhanced some effects such as the accumulation of body fat and insulin secretion and induced a greater increase in the pancreas islet size. Conclusions: Under conditions of cafeteria-style diet-induced obesity, the antagonism of the BDNF-trkB pathway had no enhanced effect on the increase in insulin secretion or pancreatic islet size.